2013
DOI: 10.3176/oil.2013.2s.13
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Assessment of Estonian Oil Shale Mining

Abstract: The global importance of and demand for oil shale are currently rapidly growing. Deposits of oil shale are widespread around the world. All this necessitates assessment of the sustainability of existing open-pit and underground mining technologies to improve oil shale mining management.The aim of the present study is to elaborate a method for assessment of the sustainability of oil shale mining to develop advanced mining technologies on this basis. Sustainability assessment has earlier been applied to two expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Overall, the common standpoint is that industrial activities must continue in Ida-Viru County, otherwise there would be even more unemployment (and consequent emigration) and even less finances for local municipalities to maintain the infrastructure and improve the quality of public services. A positive change that has occurred since the beginning of the survey is that the industrial production of oil shale has been on the rise and mining volumes have been increasing [11], which is largely due to the ever-growing importance of oil shale-based oil production on a global level. As the representatives of mining enterprises said, "Until oil shale mining takes place, scientists can come and do their research on related themes if Ida-Viru County is still alive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the common standpoint is that industrial activities must continue in Ida-Viru County, otherwise there would be even more unemployment (and consequent emigration) and even less finances for local municipalities to maintain the infrastructure and improve the quality of public services. A positive change that has occurred since the beginning of the survey is that the industrial production of oil shale has been on the rise and mining volumes have been increasing [11], which is largely due to the ever-growing importance of oil shale-based oil production on a global level. As the representatives of mining enterprises said, "Until oil shale mining takes place, scientists can come and do their research on related themes if Ida-Viru County is still alive.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted on the ecological and environmental aspects of mining and the chemical industry [7,8] and the afforestation and natural vegetation of mined areas [9]. Some studies [10][11][12] have shown that from a biodiversity perspective it is best when areas are left for nature to take over. The potential usage of underground mined areas in Estonian oil shale deposits has also been investigated [13,14].…”
Section: Introductionmentioning
confidence: 99%